2014
DOI: 10.5861/ijrse.2014.684
|View full text |Cite
|
Sign up to set email alerts
|

Constraints experienced by female students pursuing science and technology-based university programmes in their learning of science in Ghana

Abstract: This paper is part of a larger study to investigate female students in science and technology-based university (STU) programs in their motivation, perception and constraint in learning science at senior high school and consequently science and technology-based programs at the university level. The conceptual framework is rooted in Steele's concept of stereotype threat, which is the experience of anxiety or concern in a situation where a person has the potential to confirm a negative stereotype about their soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…Factors such as IQ, socioeconomic status, constraints, perception of learning science, motivation, peer interactions, teacher-student relationships, parental involvement, and personality influence academic performance [ [14] , [15] , [16] , [17] ]. [ 16 ] found that parental involvement and peer interactions were significant predictors of academic performance among university students.…”
Section: Introductionmentioning
confidence: 99%
“…Factors such as IQ, socioeconomic status, constraints, perception of learning science, motivation, peer interactions, teacher-student relationships, parental involvement, and personality influence academic performance [ [14] , [15] , [16] , [17] ]. [ 16 ] found that parental involvement and peer interactions were significant predictors of academic performance among university students.…”
Section: Introductionmentioning
confidence: 99%
“…This motivation propels them to invest time and effort in understanding complex equilibrium ideas, improving their topic comprehension, and dispelling misconceptions. Limitations, such as time constraints or restricted access to materials, can present significant obstacles to science learners' engagement with concepts of chemical equilibrium and may impede their ability to effectively correct misconceptions (Amponsah et al, 2013). Because their discipline is interdisciplinary and requires them to reconcile theoretical knowledge with practical applications in agricultural environments, agricultural science students may confront specific challenges (Taylor & Green, 2019).…”
Section: Introductionmentioning
confidence: 99%